(untitled) (Itinera, 2025)
Towards eco-friendly fashion: Eugen Fink’s lesson and new cruelty-free fabrics Fashion is compared by Eugen Fink to Japanese cherry blossoms, which although beautiful and bright the wind carries away quickly: traditionally considered ephemeral and fleeting, fashion is a cultural phenomenon to be taken seriously. The ethical challenge in fashion today is how to safeguard the planet and respect the environment. The green revolution in the fashion industry tends to replace chemical products with natural ones, among which vegan materials are of particular importance. The essay shows how the use of eco-friendly fabrics does not in any way reduce the aesthetic value of fashion items and that new recycled materials, based on circular economy, nevertheless make it possible to obtain high-quality products.